Pregnancy Complicated by an Unrepaired Ventricular Septal Defect with Eisenmenger Syndrome, Pre-eclampsia with Severe Feature, and Oligohydramnios: A Case Report and Literature Review - I Gede Agus Astawa; Abarham Martadiansyah; Nuswil Bernolian (Lembaga Publikasi Ilmiah Nusantara, 2026)
Eisenmenger syndrome represents the most advanced form of pulmonary arterial hypertension associated with congenital heart disease, in which a chronic left-to-right shunt reverses to a bidirectional or right-to-left shunt. Pregnancy in this setting carries a maternal mortality rate of 30 to 50% and is classified as modified World Health Organisation (mWHO) class IV, making pregnancy an absolute contraindication. Concurrent pre-eclampsia with severe features further increases maternal and fetal risks. We report a 20-year-old primigravida at 30 weeks of gestation presenting with progressive dyspnea, hypertension, and central cyanosis. She had had an unrepaired congenital heart defect since infancy. On admission, blood pressure was 156/95 mmHg, respiratory rate 39 breaths/min, and peripheral oxygen saturation 85% despite oxygen therapy with a non-rebreather mask. Physical examination revealed a grade 4/6 systolic murmur with fixed splitting of the second heart sound, proteinuria, and digital cyanosis. Transthoracic echocardiography demonstrated a large ventricular septal defect with bidirectional shunting, confirming Eisenmenger syndrome. The diagnosis was unrepaired ventricular septal defect complicated by Eisenmenger syndrome, pre-eclampsia with severe features, and severe oligohydramnios. After multidisciplinary stabilization, an emergency cesarean section under general anesthesia delivered a live preterm female infant. A postplacental intrauterine device was inserted for contraception. The postpartum course was complicated by persistent hypoxemia requiring intensive cardiac care. This case highlights the importance of preconception counseling, early risk stratification, multidisciplinary management, timely delivery, meticulous peripartum care, and effective postpartum contraception in women with congenital heart disease.